You are on page 1of 3

α β

α β U ( X, Y ) = X • β Y α sa I

U(X, Y ) =X

β

Y

α

sa I =

P X

X +

P Y

Y

L

=

X

β

Y

α

+ λ(I

P X

X

P Y

Y )

L

=

X β Y α + λI λP X X λP Y Y

X L =βX β1 Y α λP X = 0

Y L =αX β Y α1 λP Y = 0

L

∂λ

=I P X X P Y Y

= 0

TMS ≡ −

UM X

UM Y

=

P X

P Y

λ = λ

 

λ =

βX β1 Y α

P X

 

αX β Y α1

 

λ =

P Y

αX β Y α1

=

P X

P Y

βX β1 Y α

P X

 
 

=

αX β Y α1

P Y

 

βY

P X

=

αX

P Y

βX β1 Y α

βX β1 Y α λP X = 0

αX β Y α1 λP Y = 0

P X X

 

βP Y Y

=P X X

α

I P X X P Y Y

=

0

I βP Y Y

α

= P Y Y

I = P Y Y + βP α Y Y

 

I =

αP Y Y + βP Y Y

 

α

I =

P Y Y (α + β)

α

αI

(α + β)P Y

=Y

P Y Y

I P X X P Y Y

= 0

 

αI

(α +

β) =P Y Y

 

αI

 

αI

I

(α +

β) = P X X

I(α + β) αI

= P X X

(α + β)

 

βI

(α + β)P X

= X

I P X X

(α + β) = 0